Face-arm-trunk-leg sensory loss limited to the contralateral side in lateral medullary infarction: a new variant. Issue 2 (1st August 1998) - Vuadens, Ph; Bogousslavsky, J
Abstract : Two patients are reported on who experienced loss of pain and temperature sensation in the entire contralateral hemibody but sparing the ispsilateral face (pure sensory stroke pattern) related to acute lateral medullary infarction. In both patients MRI showed a notch-like retro-olivary ischaemic lesion in the ventromedial tegmentum with preservation of the far lateral medulla. The mediolateral lesion involved the crossed lateral spinothalamic tract and the ventral trigeminothalamic tract, corresponding to sensory loss in the contralateral face, arm, and upper trunk. The ventrolateral extension of infarct damaged the far lateral part of the spinothalamic tract, corresponding to sensory loss in the contralateral lower trunk and leg. The findings suggest that hemisensory loss of the spinothalamic type involving—and limited to—the whole hemibody can occur in infarction in the lower brainstem. This form of pure sensory stroke may be classified as type IV of sensory loss in lateral medullary infarction.